The Role of Good Corporate Governance in Stock Price Determination: Evidence from BRI - Nurul Sitio; Jovia Tatum (PT Agung Media Publisher, 2025)
Corporate governance refers to the mechanisms and processes that direct and control a company to ensure its operations are efficient and aligned with its objectives. In the context of BRI Bank, the corporate lending program poses a significant risk to its financial stability, especially amidst the ongoing economic crisis. The deterioration in the quality of non-performing loans (NPLs) has implications for evaluating asset and debt risk quality. This study employs a quantitative research method to measure data and generalize the results from a sample to the broader population. The sample consists of BRI Bank companies for the period 2017–2023. A census technique is applied, and the data is analyzed using panel data analysis to assess the relationship between corporate governance and stock prices. The findings reveal that good corporate governance has a significant effect on stock prices when considered collectively. However, when the corporate governance variable is examined individually, it does not show a significant impact on stock prices. These results suggest that while good corporate governance contributes to stock price performance in a combined context, its isolated effect is not as pronounced. The findings highlight the importance of comprehensive governance practices in influencing financial outcomes, particularly in the face of economic challenges.